Organic Fingerprint Powders Based on Fluorescent Phloxine B Dye. - Sodhi, G. S.; Kaur, Jasjeet (Defence Science Journal, 2013)
Novel fingerpript powders based on organic dye (phJoxine B) have been prepared using insoluble salts as adhesive matrials in place of costly resinous polymers (which most conventional powders incorporate). Sharp and clear prints have been developed on a wide range of surfaces, such as paper, I plastic, glass, bakelite, enamelled metal and polished wood. The fluorescent nature of phloxine B assists in developing weak prints und.er ultraviolet light which can assist a forensic scientist for lifting  fingerprints frqm the scene of crime and also a defence scientist for establishing the identity of deceased native soldiers as well as of prisoners of war.